(untitled) (AYUSHDHARA, 2024)
Arsha, commonly known as haemorrhoids, is a prevalent medical condition characterized by dilated blood vessels in ano rectal region and they can cause bleeding, pain, mucous discharge, discomfort etc. The primary causes of Arsha include increased pressure on the rectal veins, commonly attributed to chronic constipation, prolonged sitting, and straining during bowel movements. Genetic predisposition and certain lifestyle factors, such as a sedentary lifestyle and low fiber diet, can also contribute to the development of haemorrhoids. Arsha requires a surgical technique in modern treatment, such as haemorrhoidectomy, rubber band ligation, and so on, but after sometime of excision there is great possibility of reappearance of the disease. But in Ayurveda, fourfold management of Arsha has been indicated viz., Bheshaja, Kshar karma, Agni karma and Shastra karma according to chronicity and presentation of the disease. In this case study, a 40 years old female patient presented with complaints of some mass coming out during defecation, bleeding, pain and mucous discharge while passing stool to the Shalya OPD, Rishikul Campus, Uttarakhand Ayurved University Haridwar. The patient was treated successfully with Kshar karma application. The pile mass, per rectal haemorrhage and mucous discharge was gone in 7 days and the patient was free of all symptoms within 15 days. The findings revealed that there are maximum advantages which are shared in this case study.